REAKSI PASAR MODAL TERHADAP PENGUMUMAN KEBIJAKAN PSBB : (EVENT STUDY PADA PERUSAHAAN PAKAIAN DAN BARANG MEWAH) - Pramita Sari, Devi; Sari, Devi Pramita; Lating, Ade Irma Suryani (Jurnal Akuntansi, 2024)
This research examines the information content in government announcements regarding the implementation of Large-Scale Social Restrictions. Signaling theory assumes that published announcements are necessary signals or information for investors to make decisions regarding investment. The research methodology used is quantitative, using secondary data in the form of daily closing prices, stock trading volume, number of shares in circulation, and the IHSG index of clothing and luxury goods sector companies listed on the Indonesia Stock Exchange in 2020. The duration of observation is 30 days, starting from before the announcement and continuing 30 days after the announcement. The Kolmogorov-Smirnov normality test and paired sample t-test were used to test the hypothesis. The research results show no significant difference in the average actual return, average abnormal return, and average trading volume activity variables before and after implementing the Large-Scale Social Restrictions policy. These results show that the market did not react to the announcement of implementing the Large-Scale Social Restrictions policy because market players tended not to capture the information.